Postabortion Contraceptive Acceptance Rate and Its Determinants among Women Receiving Abortion Service before Discharge from the Health Facilities in Harar, Eastern Ethiopia - Endalkachew Atnafu; Biftu Geda; Lemessa Oljira; Genanaw Atnafe; Dawit Tamiru; Abdi Birhanu; Getahun Tiruye; Haregeweyn Kibret; Adera Debella (Hindawi Limited, 2022)
Background. Annually, around 121 million unintended pregnancies occur in the world and more than 73 million encountered abortion. Ethiopia is also losing 19.6% of mothers due to unsafe abortion. Despite that postabortion contraceptive service is a climactic entry point for the prevention of unwanted pregnancy and associated deaths, the service magnitude and determinants immediately before discharge are not characterized well in Ethiopia. Hence, this study aimed to assess the magnitude of postabortion contraceptive utilization and associated factors among women receiving abortion care service before being discharged from health facilities in Harar, Eastern Ethiopia. Methods. A facility-based cross-sectional study was conducted among 390 women receiving abortion care services. At discharge, data about contraceptive acceptance and related maternal characteristics were collected. A binary logistic regression model was used to assess the association between independent and dependent variables (postabortion contraceptive utilization). Analysis was done with SPSS 22. Statistical significance was considered at P<0.05. Result. The overall prevalence of postabortion contraceptive utilization was 81.5% (95% CI: 77.9, 85.4). Being unmarried (AOR, 0.05; 95% CI (0.02, 0.16)), having no history of previous abortion (AOR, 0.11; 95% CI (0.04, 0.34)), being multigravida (AOR 8.1; 95% CI (2.20, 13.40), lacking desire to have an additional child (AOR, 6.3; 95% CI (2.65, 15.34), and history of family planning use (AOR, 17.20; 95% CI (6.5, 38.60)) were determinants of postabortion contraceptive utilization before being discharged from the health facilities. Conclusion. Postabortion contraceptive utilization in Harar health facilities still needs improvement as per the WHO and national recommendations. Therefore, the family planning provision strategies should be convincing and friendly, especially for unmarried mothers, and those who had no history of abortion should be counseled in friendly and systematically convincing schemes for enabling them to take the service before discharge from the health facility.